Using NOMA scheme for the management of interference and the improvement of performance in 5G networks - Christos Bouras; Vasileios Kokkinos; Georgios Tzioumanis (The 13th International Congress on Ultra Modern Telecommunications and Control Systems and Workshops (ICUMT 2021), October 25 – 27, 2021 Virtual event, 2021)
The new generation of 5G networks, compared to 4G networks, is a very important example of change in achieving very high frequencies in the carrier with huge bandwidth, high densities with a huge number of antennas and improved quality of services, making effective interference management necessary. In this paper, we present the contribution of the Non-Orthogonal Multiple Access (NOMA) scheme to improving the performance of 5G networks. We refer to the technique of sequential interference cancellation applied to some NOMA formats, compare NOMA and Orthogonal Multiple Access (OMA) formats in terms of the capabilities they offer users and NOMA's significant contribution to Multiple-Input Multiple-Output (MIMO) technology and compare three basic NOMA formats in three different resource and user reporting scenarios. Finally, we present the results of the simulations of the above comparisons and analyze the contribution of each scheme to the improvement of the system performance.